2019
DOI: 10.5114/pedm.2019.84709
|View full text |Cite
|
Sign up to set email alerts
|

Clinical determinants of the remission phase in children with new-onset type 1 diabetes mellitus in two years of observation

Abstract: Possibilities of prolonging endogenous insulin production during the "remission phase" of type 1 diabetes (T1DM) have been the focus of much interest in recent research. The aim of the study was to describe the course of clinical remission in children with new-onset type 1 diabetes and to compare the selected markers affecting the presence of partial clinical remission (CR), focusing, among others, on physical activity before/during diagnosis. Material and methods: We recruited 82 children (aged 10 ±3.72 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Among the studied population, we did not find any case of complete remission, which is consistent with some previous studies (2,4,21). However, some other authors reported complete remission cases (10,23,25).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the studied population, we did not find any case of complete remission, which is consistent with some previous studies (2,4,21). However, some other authors reported complete remission cases (10,23,25).…”
Section: Discussionsupporting
confidence: 93%
“…Most often, the symptoms of type 1 diabetes mellitus (T1D), caused by progressive, autoimmune destruction of pancreatic β-cells leading to insulin deficiency, appear when more than 70% of β-cells are damaged ( 1 ). This destruction begins several years before the clinical diagnosis of diabetes, but some of these cells can still be functional even decades after the onset ( 2 4 ) with detectable C-peptide after as long as 50 years of diabetes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, the influence of exercise on C-peptide secretion was marked. [52,53] PA related health benefits in T1D are indisputable, and it should be advised as a part of routine management in all patients since diabetes onset. Exercise not only promotes fitness but also reduces daily insulin demand, improves lipid profile, endothelial function and overall well-being, finally resulting in reduction of cardiovascular risk and mortality.…”
Section: Mody Diabetesmentioning
confidence: 99%
“…Moreover, C-peptide levels presented in some studies as an independent factor of partial remission and is correlated with its duration ( 13 , 14 ). The phenomenon of partial remission (PR), also known as the honeymoon phase, occurs in a number of patients who experience a transient reduction in insulin requirements in parallel with achieving proper metabolic control after the initiation of effective insulin therapy ( 15 ). PR is defined as a daily insulin requirement (DIR) of <0.5 units per kg of body weight and HbA1c <7% ( 16 ).…”
Section: Introductionmentioning
confidence: 99%